INFLUENCE OF CHRONIC STRESS ON FORM-DEPRIVATION MYOPIA - Ulyanova, N.A.; Dumbrova, N.E.; Molchanyuk, N.I. (World of Medicine and Biology, 2014)
To investigate changes in the linear dimensions of eyeball, the morphological features of sclera and retina in rats with form-deprivation myopia and rats with form-deprivation myopia and chronic stress. Chronic stress alters the outcomes of experimental form-deprivation myopia. The increasing axial sizes of eye was significantly higher in state of chronic stress than in the myopia model without the stress. Morphological and functional abnormalities in the retina and the sclera were more pronounced also. In experimental myopia in state of chronic stress not only damaged neurons and their processes, but also glial cells of the retina. Collagen fibers disorganization in sclera, fibroblasts function disorders pronounced more than in form-deprivation myopia without stress.